A computational comparison of NH3/O2 and CH4/O2 non-premixed laminar flames. (1st February 2022) - Yang, Wenkai; Al Khateeb, Ashraf N.; Kyritsis, Dimitrios C.
Highlights: Expansion in ammonia flames much weaker than methane. Nitrogen oxidation stops with molecular nitrogen, minute quantities of NOx . Low-strain flames "partially burning flames" with low Damköhler numbers. Abstract: The structure of non-premixed, laminar, counterflow NH3 /O2 flames was studied and compared with the structure of CH4 /O2 flames. A commercially available computational tool was utilized through the introduction of ammonia and methane chemistry in order to compute the flow fields of strained flames. The tool was validated by comparing with previously published results for CH4 flames and by employing two different mechanisms for NH3 oxidation kinetics. It was shown that NH3 flames achieve lower maximum temperature and narrower high-temperature area compared to CH4 flames, which was attributed to much less heat release from the NH3 oxidization process. This is due to the fact that NH3 oxidation proceeds through a chemical path drastically different than the one of CH4 and is completed with the formation of N2 as an equilibrium product, without substantial formation of nitrogen oxides. The structure of the CH4 and NH3 flames were compared for mildly strained flames and it was shown that, despite its much slower kinetics, ammonia can sustain near-equilibrium flames, even for relatively small values of the Damköhler number.